Exotic amphibians and reptiles of the United States - Meshaka, Walter E., 1963-; Collins, Suzanne L.; Bury, R. Bruce; McCallum, Malcolm L. (University Press of Florida, 2022)
"The first complete field guide to the exotic amphibians and reptiles established in the continental United States and Hawaii, this book provides practical identification skills and an awareness of the environmental impacts of these species"--